Resonant photoacoustic spectrometer enhanced by multipass absorption for detecting atmospheric CH4 at the ppb-level - Liu, Qiang; Sun, Yi; Qiu, Xuanbing; Guo, Guqing; Li, Lin; Gong, Ting; Li, Chuanliang (Frontiers in Chemistry, 2022)
A resonant photoacoustic spectrometer (PAS) was developed for detecting trace atmospheric CH4. The sensitivity of the PAS was significantly increased via a Herriott-type multipass cell with a beam pattern concentrated in the cavity. The effective optical pathlength of the PAS can be optimized to 6.8 m with 34 reflections and a diameter of 6 mm. A distributed feedback diode laser at 1,653 nm was employed as the light source, and wavelength modulation spectroscopy was used for the 2nd harmonic signal to reduce the noise of the system. The resonant cell of PA and optimal modulation frequency were obtained by varying the measurements. In comparison with a single path, the sensitivity of the multipass strategy was improved 13 times. To evaluate the long-term stability and minimum detection limit (MDL) of the system, an Allan variance analysis was performed, and the analysis illustrated that the MDL accomplished 116 ppb at an average time of 84 s. The system was utilized for 2 days test campaign to validate the feasibility and robustness of the sensor. The system provides a promising technique for online monitoring of greenhouse gasses.